Peel more and unwrap less: a contextualized and interdisciplinar approach to Science education (Research, Society and Development, 2019)
Proper nutrition is essential for achieving health and quality of life, as many diseases in today's society are directly related to our habits and can be prevented through minor daily changes. To this end, this article aims to present the project experience report developed with a group of students of youth and adult education, which used labels to quantify the sugars in foods, providing reflection on the composition of foods. and its nutrients as a starting point for the healthy eating approach. Through the reported experience, it becomes possible to verify the importance of promoting spaces for discussion in schools about the practice of a balanced diet, so that students may take a critical stance regarding the information and food to be consumed.